2022
DOI: 10.1186/s13287-021-02681-3
|View full text |Cite
|
Sign up to set email alerts
|

Human MuStem cells repress T-cell proliferation and cytotoxicity through both paracrine and contact-dependent pathways

Abstract: Background Muscular dystrophies (MDs) are inherited diseases in which a dysregulation of the immune response exacerbates disease severity and are characterized by infiltration of various immune cell types leading to muscle inflammation, fiber necrosis and fibrosis. Immunosuppressive properties have been attributed to mesenchymal stem cells (MSCs) that regulate the phenotype and function of different immune cells. However, such properties were poorly considered until now for adult stem cells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 109 publications
0
2
1
Order By: Relevance
“…Interestingly, selective inhibition of COX-2 abrogates the effects of ADSC spheroid extracts and ADSC monolayer extracts on inducing T regulatory cell expansion. In comparison with a prior study that reported COX-2 is important for the suppression of T cell proliferation 38 , our results indicated that COX-2 inhibition by celecoxib was incapable of attenuating the immunosuppression efficiency of MSCs on activated T cell proliferation. Therefore, COX-2 is one of the key factors that partially mediates the immunomodulation effects of ADSC extracts.…”
Section: Discussioncontrasting
confidence: 70%
“…Interestingly, selective inhibition of COX-2 abrogates the effects of ADSC spheroid extracts and ADSC monolayer extracts on inducing T regulatory cell expansion. In comparison with a prior study that reported COX-2 is important for the suppression of T cell proliferation 38 , our results indicated that COX-2 inhibition by celecoxib was incapable of attenuating the immunosuppression efficiency of MSCs on activated T cell proliferation. Therefore, COX-2 is one of the key factors that partially mediates the immunomodulation effects of ADSC extracts.…”
Section: Discussioncontrasting
confidence: 70%
“…Inhibition of the M1 macrophage phenotype and promotion of the M2 phenotype was thought to contribute to tissue regeneration ( Chen et al, 2021 ). In addition, human MuSCs, a type of muscle SCs, can secrete mediators such as heme oxygenase-1 and prostaglandin E2 to inhibit T lymphocyte proliferation, induce Treg-like cell production and suppress the cytotoxic response of CD8+ T lymphocytes ( Charrier et al, 2022 ). Thus, SCs can produce various mediators to act on multiple immune cells, including macrophages and T cells, and play a pivotal role in regulating the immune microenvironment.…”
Section: Applications Of Sc Therapymentioning
confidence: 99%
“…MSCs enhance Treg immunosuppression through contact-dependent interactions that are partly mediated by MSC-expressed CD80 ( Mittal et al, 2022 ). Myogenic hMuStem cells suppress T cell activity and promote Treg production through paracrine or intercellular contacts ( Charrier et al, 2022 ). Thus, hMuStem cells are potent immunomodulators.…”
Section: Update On the Stem Cell Interaction Mechanism Theorymentioning
confidence: 99%